Viscosity Behavior of Solutions of Some Potassium Salts in Dimethyl Sulphoxide –Water mixture (Baghdad Science Journal, 2010)
The present work includes a study of viscosity of solutions containing Potassium Chloride and Potassium Bromide in Dimethyl Sulphoxide and water as solvent (containing 60% w/w DMSO).The study was carried out at six different temperatures. The applicability of Jones- Dole equation has been discussed. Solute –solvent interaction was discussed in terms of ionic size, charge, and shape of solute molecules.